Serum interleukin 18 and tumour necrosis factor-α levels are increased in Behcet's disease - Oztas, M. O.; Onder, M.; Gurer, M. A.; Bukan, N.; Sancak, B. (Clinical and experimental dermatology, 2005)
Summary Inflammation in Behcet's disease is thought to be mediated by cytokines derived from T‐helper type 1 (Th1) lymphocytes. In this study, we tried to determine serum interleukin (IL)‐18 and tumour necrosis factor (TNF)‐α levels of patients with Behcet's disease. Twenty‐seven patients with active Behcet's disease, and 20 healthy control subjects were included in this study. Differences between mean serum IL‐18 and TNF‐α level of patients with Behcet's disease were significantly increased when compared with the control group. A significant correlation was found between serum IL‐18 and TNF‐α levels of Behcet patients (rs = 0.627, P < 0.0001). IL‐18 and TNF‐α levels may be related to disease pathogenesis. Increased levels of IL‐18 also support Th1 predominance in Behcet's disease.